Guanacaste: el surgimiento de un discurso regionalista, 1900-1926 - Buska, Soili (Revista de historia., 2006)
Based mainly on journalistic sources, the article analyzes the emergence of the Guanacastecan regionalist discourse in Costa Rica in the first decades of the twentieth century. Special attention is paid to the conjuncture of the commemoration of the centenary of the annexation of the Partido de Nicoya to Costa Rica that initially woke up great hopes but soon became a bitter disappointment for the promoters of the incipient regionalism. The frustration caused by the way in which the official commemoration took place deepened the critical reflection on the historical relationship between the national State and the province and consolidated the discourse on Guanacaste as the province lmjust1y abandoned by the Costa Rican State.